Private Policing and Surveillance of Catholics: Anti-communism in the Roman Catholic Archdiocese of Toronto, 1920-1960 - Maurutto, Paula (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1997)
Abstract This study examines the private policing and surveillance tactics adopted by the Roman Catholic Archdiocese of Toronto to prevent the spread of communism, particularly within its congregation. Catholic "spies" and informants kept the Church abreast of communist maneuverings in ethnic communities, religious organizations, and on university campuses. An extensive moral and educational campaign was launched by the Church to create a bulwark against the Reds. These actions highlight the historical role of voluntary organizations in the policing of citizens and the maintenance of national security. Policing is redefined as a phenomenon that operated beyond the exclusive domain of the state. The analysis seeks to introduce a broader notion of national security and policing by examining the interplay between public and private institutions.